Engineering of Human Skeletal Muscle With an Autologous Deposited Extracellular Matrix - Thorrez, Lieven; DiSano, Katherine; Shansky, Janet; Vandenburgh, Herman (Frontiers in Physiology, 2018)
Adult skeletal muscle progenitor cells can be embedded in an extracellular matrix (ECM) and tissue-engineered to form bio-artificial muscles (BAMs), composed of aligned post-mitotic myofibers. The ECM proteins which have been used most commonly are collagen type I and fibrin. Fibrin allows for in vitro vasculogenesis, however, high concentrations of fibrinolysis inhibitors are needed to inhibit degradation of the ECM and subsequent loss of BAM tissue structure. For in vivo implantation, fibrinolysis inhibition may prove difficult or even harmful to the host. Therefore, we adapted in vitro culture conditions to enhance the deposition of de novo synthesized collagen type I gradually replacing the degrading fibrin ECM. The in vitro viscoelastic properties of the fibrin BAMs and deposition of collagen were characterized. BAMs engineered with the addition of proline, hydroxyproline, and ascorbic acid in the tissue culture medium had a twofold increase in Young’s Modulus, a 2.5-fold decrease in maximum strain, and a 1.6-fold increase in collagen deposition. Lowering the fibrin content of the BAMs also increased Young’s Modulus, decreased maximum strain, and increased collagen deposition. Tissue engineering of BAMs with autologous ECM may allow for prolonged in vivo survival.